Corporate Governance , Characteristics on Dividend Policy: Evidence From Indonesia - Hendy Satria; Muhammad Isa Alamsyahbana; Rachmad Chartady; Fauzi Fauzi; Novi Chandra Saputra (Yayasan Ilomata, 2021)
This research aims to explore the instability of the dividend distribution policy of listed companies on the Indonesian stock exchange. Researchers use several main variables as indicators to measure their impact on dividend policy. The samples used are 75 manufacturing companies. Data analysis technology uses descriptive statistical analysis and E Views 6. 0 as data processing tools. The results of this study show that the audit committee has a negative and insignificant influence on dividend policy. At the same time, independent committees, public interest, company size and profitability have a positive and significant impact on dividend policy.